Les Français, c'est les autres - Ulad, Mohamed; Wekstein-Steg, Isabelle (France : Une Production, 2015)
‘The French are the Others’ offers us access to what they think, those that we talk about interruptedly but never hear, or too rarely hear, the youth of the suburbs. The directors, Mohamed Ulad, from Arabic descent, and Isabelle Wekstein-Steg, from Jewish descent, ask students in a suburban high school, “who is the “Jew”? and “who is the “Arab”?” The prejudices come thick and fast. This documentary offers an understanding into the lives of these teenagers living in a ghetto. Not only a spatial ghetto, but a ghetto of thought and imagination. They are alone, cut off from the world, with their stereotypes and their fantasies, which they too rarely have the occasion to confront with the reality. But the problem is that most of them don’t feel that they are French. Their nationality is French but they assert and repeat that they don’t feel French.
Verzio Film Festival Submission
Keywords: Documentary films